TEKNIK DAN ANALISIS KELAYAKAN FINANSIAL PENGOLAHAN LIMBAH GAHARU DI KOTA METRO LAMPUNG - Khairunnisa, Shafira; Lidiawati, Ina; Meiganati, Kustin Bintani (Universitas Nusa Bangsa, 2021)
Non-timber forest products (NTFPs) are expected to be another alternative in forest utilization, one of the commodities that has a high selling value is agarwood. Agarwood is the most expensive aromatic ingredient in the world. But there are still many people who do not know about the advantages of gaharu, so this research aims to provide an overview to the wider community regarding processing techniques and calculation of the analysis of the cost of developing an agarwood oil processing business. This study was carried out in the agarwood oil processing household industry in Mero Selatan sub-district, Lampung Province from January 2020 to April 2020 using quantitative descriptive research methods. Data obtained through interviews and observations, as well as business feasibility data analysis carried out by calculating the analysis of Net Present Value, Benefit Cost Ratio and Payback Period.The results showed that the agarwood oil refining business was declared feasible, with a positive NPV analysis or greater than zero of Rp. 1,575.368.554 ,-, BCR analysis is Rp. 13,9 where every Rp. 1 issued then has a benefit of Rp. 13,9, and the Payback Period for 5 months 19 days does not exceed the planned business period.